ANALISIS DISIPLIN KERJA PEGAWAI YANG DIPENGARUHI OLEH KEPEMIMPINAN DAN BUDAYA ORGANISASI PADA DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN DONGGALA - Arianto, Arianto; Kaseng, Saharuddin; Adda, Harnida Wahyuni (Katalogis, 2018)
The study intends to determine and analyze simultaneous influence of leadership and organizational culture on work discipline of officials in the Department of Manpower and Transmigration, Donggala District and partial influence Â of leadership on work discipline, as well as the inflence of organizational culture on work discipline of officials in Manpower and Transmigration office, Donggala District. Respondents consist of 48 officials. Method of study is causal descriptive with multiple liear regressions analysis. The result finds that leadership and organizational culture simultaneously have significant influence on work discipline with R-square value of 0.567 in sig 0.000. Leadership has significant influence on work discipline with coefficient regression value 0,293 on sig 0.013 and the influence of organizational culture on work discipline determined by coefficient regression value of 0.613 on sig. 0.000.